2020
DOI: 10.1111/bjhp.12474
|View full text |Cite
|
Sign up to set email alerts
|

Reasoned action approach and compliance with recommended behaviours to prevent the transmission of the SARS‐CoV‐2 virus in the UK

Abstract: Objectives. To examine associations between demographics, people's beliefs, and compliance with behaviours recommended by the UK government to prevent the transmission of the SARS-CoV-2 virus that causes COVID-19. Design. A two-wave online survey conducted one week apart during the national lockdown (April, 2020). Measures. A sample of 477 UK residents completed baseline measures from the reasoned action approach (experiential attitudes, instrumental attitudes, injunctive norms, descriptive norms, capacity, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 26 publications
11
78
0
Order By: Relevance
“…To date, we have published 17 COVID-19 papers (Bacon & Corr, 2020;Gibson Miller et al, 2020;Grover, McClelland, & Furnham, 2020;Horesh, Kapel Lev-Ari, & Hasson-Ohayon, 2020;Howard, 2020;Lades, Laffan, Daly, & Delaney, 2020;Lauri Korajlija & Jokic-Begic, 2020;Lin et al, 2020;Marinthe, Brown, Delouvee, & Jolley, 2020;McElroy et al, 2020;Niepel, Kranz, Borgonovi, Emslander, & Greiff, 2020;Norman, Wilding, & Conner, 2020;Olagoke, Olagoke, & Hughes, 2020;Rubaltelli, Tedaldi, Orabona, & Scrimin, 2020;Shevlin et al, 2020;Williams et al, 2020), which have addressed a variety of topics including: the use theoretical models (COM-B and social cognition models) to understand and predict COVID-19 health behaviours (Gibson Miller et al, 2020;Lin et al, 2020;Norman et al, 2020), risk perception (Niepel et al, 2020;Olagoke et al, 2020), and psychological distress (Horesh et al, 2020;Lades et al, 2020;McElroy et al, 2020;Shevlin et al, 2020). presented a systematic method for rapidly responding to priority SARS-CoV-2 policy questions.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, we have published 17 COVID-19 papers (Bacon & Corr, 2020;Gibson Miller et al, 2020;Grover, McClelland, & Furnham, 2020;Horesh, Kapel Lev-Ari, & Hasson-Ohayon, 2020;Howard, 2020;Lades, Laffan, Daly, & Delaney, 2020;Lauri Korajlija & Jokic-Begic, 2020;Lin et al, 2020;Marinthe, Brown, Delouvee, & Jolley, 2020;McElroy et al, 2020;Niepel, Kranz, Borgonovi, Emslander, & Greiff, 2020;Norman, Wilding, & Conner, 2020;Olagoke, Olagoke, & Hughes, 2020;Rubaltelli, Tedaldi, Orabona, & Scrimin, 2020;Shevlin et al, 2020;Williams et al, 2020), which have addressed a variety of topics including: the use theoretical models (COM-B and social cognition models) to understand and predict COVID-19 health behaviours (Gibson Miller et al, 2020;Lin et al, 2020;Norman et al, 2020), risk perception (Niepel et al, 2020;Olagoke et al, 2020), and psychological distress (Horesh et al, 2020;Lades et al, 2020;McElroy et al, 2020;Shevlin et al, 2020). presented a systematic method for rapidly responding to priority SARS-CoV-2 policy questions.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
“…Others have used an integrated social cognition model to explain preventative COVID-19 behaviours, reporting that coping planning and action planning had the strongest associations with behaviour although other predominant factors were found to include behavioural intentions, self-efficacy, and perceived behavioural control (Lin et al, 2020). Norman et al (2020) utilized the Reasoned Action Approach examining associations between demographics, people's beliefs, and compliance with transmission reducing behaviours recommended by the UK government during the national lockdown. Baseline levels of confidence (capacity) were associated with compliance to each of the five recommended behaviours one week later.…”
Section: Bjhp: Covid-19 Health Psychology Researchmentioning
confidence: 99%
“…The broader behaviour change literature and theoretical models suggest that self-efficacy (confidence to perform a behaviour), attitudes towards the target behaviour, social norms and risk perception, often play an important role in uptake of health behaviours (8-11). However, to date, only a few peer-reviewed studies in Australia, the United Kingdom, and the United States have investigated whether psychosocial factors tied to behavioural theories can predict continued adherence to COVID-19 prevention behaviours (12-14). For example, three studies reported that intention and confidence to perform/maintain a COVID prevention behaviour (self-efficacy) were consistently associated with self-reported behaviour one week later (12-14).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, only a few peer-reviewed studies in Australia, the United Kingdom, and the United States have investigated whether psychosocial factors tied to behavioural theories can predict continued adherence to COVID-19 prevention behaviours (12-14). For example, three studies reported that intention and confidence to perform/maintain a COVID prevention behaviour (self-efficacy) were consistently associated with self-reported behaviour one week later (12-14). Two of these studies also measured action planning and self-monitoring and observed that these constructs predicted distancing behaviour(12, 13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation